The device has a large storage space. Geographic system (GIS) - علي, د.خالد ولي علي (Sulaimani Journal for Humanities, 2025)
The spatial distribution patterns of rural settlements are an important indicator of population geography, reflecting the forms of distribution and the factors influencing their spacing. This research focuses on studying the distribution patterns of rural settlements in the Garmian Administration, along with analyzing the factors affecting this distribution. The study area is an administrative unit within the Kurdistan Region, covering approximately 6,000.1 km², and lies between latitudes 34°15'33" and 35°11'05"N, and longitudes 44°29'41" and 45°54'20"E. This research aims to highlight the spatial distribution patterns of rural communities in the Garmian Administration, specifically the factors influencing this distribution. Statistical and analytical methods were employed in this study, utilizing a quantitative approach with spatial statistical data. The study also employed geographic analysis tools (ArcGIS 10.8) to analyze the data using spatial analysis and statistical analysis techniques. Among the methods used were the Average Nearest Neighbor (ANN) method for analyzing distribution patterns, as well as calculating geographic distribution centers, standard distances, and directional distribution analysis. The research results yielded a set of indicators that contribute to understanding the distribution of rural settlements in the study area, with a focus on the variations caused by natural and human factors influencing this distribution.
Keywords: Distribution patterns; rural settlements; Kalar administration; Geographic Information Systems (GIS); Nearest Neighbor